The Polymorphous Return of the Tragic in J. Littell e M. Amis - Emanuela Piga (Between, 2017)
In this article I intend to analyse Jonathan Littell’s novel Les Bienveillants (2006) and Martin Amis’s novel The Zone of Interest (2014) in their dealing with the traumatic events of the Twentieth Century through literary writing and in their conveying meaning in terms of remembrance and historical awareness of collective traumas. In particular, I tackle the relationship between historical consciousness and the return of the tragic, as a way to identify in the representation of the inner rupture of the self the connection between the psychoanalytic dimension and the tragic dimension, and between private and political unconscious.